IJTIHAD DALAM LINTASAN SEJARAH (Menelusuri Pasang Surut al-Tasyri’ al-Islamiy) - Bahruddin, - - (Irtifaq, 2014)
The changes in Islamic Law depends on thefrequency of ijtihad by the mujtahid. Ijtihadactivities throughout history has been delivering inpro and contra related with ijtihad chance. Theperiod of the Prophet and the Companion, calledbe the initial phase of jurisprudence. In tabi'inperiods, during the next two or three generations,commonly called phase formation and opening offiqh. In this phase, the fiqh reached the height ofglory and gold. The next phase, considered as aphase of decline of ijtihad and closing of the doorsof ijtihad’s view. The closure of the door of ijtihadis presumably need to be reconsidered, as opposedto the reality that the needs and purposes ofcompleting a case continue to evolve with thetimes, while not all of the problems containedexplicitly and in detail in the Qur'an or Hadith.Keywords: Ijtihad, a mujtahid, closing the door of ijtihad